The influence of the psychological factors upon the entrepreneurial tendency in crisis environments - Gabriela Marcu; Cornelia Iordanescua; Eugen Iordanescua (Procedia - Social and Behavioral Sciences: PSIWORLD 2011, 2012)
We aim to determine whether the relationship of psychological factors and environmental factors affecting the entrepreneurial tendency change, due to perceptions of negative economic environment/economic crisis. The study focuses on the way in which perceptions of economic crisis and scarcity of money affects the entrepreneurial tendency of young people. We selected 152 students with Internal Locus of Control/ILC (using Rotter's Locus of Control Scale), and they were involved in four experimental scenarios. The exposure of young people with ILC in crisis conditions significantly affects their entrepreneurial tendency, while the intensity of scarcity of money has an insignificant effect.
Keywords: 330; Entrepreneurial tendency; Rotter's Locus of Control Scale; Economic Crisis; personality